Storage stability of pennywort juice as affected by high pressure and thermal processing - P. Chaikham (2018)
The physicochemical and microbiological qualities of pressurized (500 MPa/30°C/20 min) and pasteurized (90°C/3 min) pennywort juices were determined during chilled storage (4°C) for 4 months. The color parameters and pH values in both processed juices exhibited no changes upon storage. Moreover, it was found that high pressure could preserve various bioactive components including ascorbic acid, total phenolic compounds and antioxidant capacity (FRAP assay), superior than pasteurization. Asiaticoside, madecassoside and β-carotene were relatively stable on the processing and storage. The concentrations of total phenolic compounds and ascorbic acid as well as antioxidant capacity in both processed juices significantly decreased with an increasing of the storage times; however these components still retained in pressurized juice higher than pasteurized juice. The microbiological assessment displayed that standard plate count, yeasts and moulds in both processed juices were pleasingly eliminated.